Evaluation of DNA extraction methods for molecular traceability in cold pressed, solvent extracted and refined groundnut oils: Evaluation of DNA extraction methods for molecular traceability in cold pressed, solvent extracted and refined groundnut oils - KEOTSHEPILE PRECIOUS BOJANG,; APARNA KUNA,; SREERANGAM NCVL PUSHPAVALLI,; SUPTA SARKAR,; M SREEDHAR, (Journal of Oilseeds Research, 2023)
Groundnut oil (GNO)/ peanut oil is one of the agro-food products with great economic value and hence an attractive target for adulteration and mislabeling. Simple Sequence Repeats (SSR) are markers of choice for DNA fingerprinting studies as they exhibit high polymorphism due to variable number of repeats. Hence, this study was designed to evaluate and optimized a method for DNA isolation from groundnut oil and study the possibility of using the isolated DNA for molecular traceability using SSR markers. Four methods to isolate DNA from groundnut oil were evaluated. All the four methods were modified CTAB protocols, but differed in procedures forextraction, buffer compositions, amount of oil used and DNA carriers. For molecular traceability of oils, extraction and recovery of DNA from edible oil is a key step, especially in refined oils. A method that employed DNA enrichment prior to extraction with CTAB buffer yielded amplifiable DNA from cold pressed GNO, crude hexaneextracted GNO and refined GNO. The optimized method for isolation of DNA from groundnut oil is simple, efficient, less costly and reproducible when compared to chromatography and spectroscopy based techniques.